ChemInform Abstract: Free‐Amine‐Directed Alkenylation of C(sp2)—H and Cycloamination by Palladium Catalysis. Issue 19 (18th April 2013) - Liang, Zunjun; Ju, Long; Xie, Yongju; Huang, Lehao; Zhang, Yuhong
Abstract PdCl2/CuCO3‐mediated treatment of biaryl‐2‐amines with various alkenes like (II) and (VII) is found to allow a new, regio‐ and chemoselective access to phenanthridine derivatives.